Strategi Pengembangan Desa Wisata Pulau Sapi dalam Meningkatkan Perekonomian Masyarakat Lokal Perspektif Ekonomi Islam - Iswantoyo, Iswantoyo (Universitas Muhammadiyah Ponorogo, 2024)
The aim of this research is to determine the strategy for developing tourist villages in increasing the volume of visitors and the economy of local communities from an Islamic economic perspective. The research method uses descriptive qualitative where data collection techniques are by means of observation, interviews and documentation. The interviews used in this research used structured interviews, because they were based on guidelines or main questions that would be asked during the interview. The research location was carried out in the Pulau Sapi Tourism Village, Mentarang District, Malinau Regency, North Kalimantan Province. Observations were carried out on related parties such as village heads, tourist village managers and employees. The research results show that the introduction of Pulau Sapi tourist village was through social media (website, YouTube, Instagram). Various customs and cultures are displayed in every activity on Sapi Island. For tourist publications (Semolon Hot Springs, Gita River Trail) and artificial tourist publications (Dayak Ethnic Carving House, Identity Monument, Alun2 Ulung Buaye). Every time there is a busy activity, the people of Pulau Sapi always serve traditional food typical of Pulau Sapi village. By utilizing MSMEs in the local area, developing human resource potential from Pokdarwis and BUMDes for each activity will increase the community's economic activities. Islam there teaches honesty, peace and trust in carrying out activities.